2006
DOI: 10.1002/jcp.20861
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and the cytoskeleton in the neuronal modulation of transcription factor NFAT

Abstract: Transcription factor NFAT is crucial in the development of the nervous system due to its role in neuronal plasticity and survival. In this study we characterized the role of zinc and the cytoskeleton in the modulation of NFAT in neuronal cells. The incubation of cells in zinc deficient media led to NFAT activation that was inhibited by the calcium chelator BAPTA and the antioxidants (AE)-a-lipoic acid and N-acetyl cysteine, suggesting the involvement of calcium and oxidants in the initial steps of NFAT activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 56 publications
3
43
0
Order By: Relevance
“…Although a previous study has shown that the disruption of tubulin polymerization affects NFAT nuclear translocation in neural cells (13), the mode of the action remains unknown. Our present study identified the role of tubulin a as an adaptor in NFAT-importin b interaction.…”
Section: Resultsmentioning
confidence: 97%
“…Although a previous study has shown that the disruption of tubulin polymerization affects NFAT nuclear translocation in neural cells (13), the mode of the action remains unknown. Our present study identified the role of tubulin a as an adaptor in NFAT-importin b interaction.…”
Section: Resultsmentioning
confidence: 97%
“…The specificity of NF-B's requirement for dyneinbased transport was tested by examining the effect of loss of endogenous dynein on the activity of two additional transcription factors, one which is largely localized in the nucleus (CREB) and another which undergoes cytoplasmic to nuclear translocation (NFAT). Interestingly, dynein knockdown did not significantly alter either CREB or NFAT reporter activity, although it has been reported that perturbations in the microtubule network could inhibit NFAT (32). While p53 is known to use dynein (26), the transport mechanisms of many nuclear localizing molecules are either unknown or are independent of the cytoskeleton (29,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…2). Zinc deficiency in cells and fetal brain increases NFAT activation but the nuclear translocation of NFAT is impaired due to disruption of the microtubule network leading to a subsequent reduction in NFAT-dependent gene expression (Aimo et al, 2010b;Mackenzie and Oteiza, 2007). These changes in cell signaling were also observed during marginal zinc deficiency (Aimo et al, 2010b).…”
Section: Cell-signaling Cascadesmentioning
confidence: 93%